Robust Optimal Dispatching of Wind Fire Energy Storage System Based on Equilibrium Optimization Algorithm - Chen, Xiaojiao; Huang, Liansheng; Zhang, Xiuqing; He, Shiying; Sheng, Zhicai; Wang, Zhenshang; Chen, Tao; Dou, Sheng (Frontiers in Energy Research, 2021)
The uncertainty of wind resources is one of the main reasons for wind abandonment. Considering the uncertainty of wind power prediction, a robust optimal dispatching model is proposed for the wind fire energy storage system with advanced adiabatic compressed air energy storage (AA-CAES) technology. Herein, the operation constraints of the power plant and constraints of the reserved capacity are defined according to the operation characteristics of AA-CAES. Based on the limited scenario method, a solution framework is proposed to achieve the optimal robustness and economical operation of the system, which provides a new way for the application of the intelligent algorithm in the robust optimal dispatching. Specifically, a novel equilibrium optimization algorithm is employed to solve the optimal dispatching problem, which has good global search performance. The proposed solution is validated through simulations based on the IEEE-39 node system. The simulation results verify the effectiveness of the proposed dispatching model and the intelligent solver.